Emerging identity: Žižkov district as a framework of collective memory - Stoklásek, Rostislav (Vysoké učení technické v Brně, Fakulta architektury, 2022)
The paper introduces understanding architecture as a mental image, an imprint of a physical space in collective memory. It focuses on the urban qualities of the Žižkov district, a late 19th century housing development in Prague, acknowledged in discussions over its replacement by a prefabricated housing estate in late 1980s. A theoretical concept introduced by Maurice Halbwachs is applied in order to propose a perspective indicating that these qualities developed gradually over time, as Žižkov was becoming a framework of collective memory.
Keywords: urban planning; history; Prague; clearance; remodelling; urban renewal